Design of a multi-feed slot antenna - Chew, Kenny Chia Jong. (2010)
This report presents the design and study of a multi-feed slot antenna using the cavity-backed slot configuration. With the use of a single rectangular slot, operations at the various operating frequencies can be accurately tuned by adjustment made at a single accessible surface. The slot antenna is fed by two microstrip line on the top of the substrate for the 2.1- GHz, 2.4- GHz and 5-GHz bands. Simulations were carried out using the Ansoft’s high frequency structure simulator and a prototype is fabricated and tested. The measured returned losses are -13.5dB, -15.2dB and -15.4dB for the 2.1-GHz, 2.4-GHz and 5-GHz bands respectively. There is also a positive measured gain at 5GHz when the multi-feed slot antenna was placed at 0o and the horn antenna placed at 90o.